(untitled) (Advances in Civil and Architectural Engineering, 2025)
This study evaluates the primary-secondary structure interaction in three-dimensional single- and multi-story steel frame structures. A novel and practical approach was proposed to consider the effect of secondary systems. Additionally, a technique was developed to lower the time period of coupled structures. This is particularly helpful in high-rise buildings when exposed to earthquakes. Five types of steel frames were designed, fabricated, and subjected to seismic loading. The experimental models were exposed to ground motion excitations and the finite element models were subjected to nonlinear dynamic time-history analyses. An excellent agreement between the two approaches were observed. According to the results, infill wall displacements and accelerations were considerably reduced by utilizing the deformable wall setting. In this regard, the story displacements and accelerations decreased from 209 to 211 mm and 17,8 to 18,0 meter per square second when secondary systems were used. In addition, free vibrations of the frames were considerably reduced when the concentrated mass secondary systems were implemented.